Enhancing skill and performance in resistance training - Kompf, J. (Strength and Conditioning Journal, 2016)
Enhanced muscular strength is beneficial to athletes because of improved rate of force development. For athletes to progress in resistance training, it is of paramount importance that proper form is taught. There are many aspects of weight lifting that contribute to successful performance. Having proper form is one of these aspects. It is the coach's job to teach resistance training exercises that require skill and also to maximize performance for the exercises they are teaching. This review covers exercise selection, modeling, focus of attention, and augmented feedback for the sport and performance coach.